Barriers to geography learning and teaching in grade 12 in the Limpopo Province - Maduane, Leshabela Herbert (University of Limpopo, 2016)
The purpose of this research was to investigate teachers’ professional proficiency in terms of geography as a subject and English as the language of learning and teaching, the level of difficulty of the textbooks in terms of their difficulty of terminologies and structure, and the impact of code-switching from LoLT into local African languages on learners’ growth in geographical terminologies and communicativeness in English thinking in geography. These issues were considered by the researcher as barriers to learning and teaching of geography in grade 12 in the Limpopo Province. For the investigation of the barriers, the researcher chose research design comprising qualitative, quantitative, explorative and descriptive approaches pertinent to the study. The central figure in the investigation was the learner; the study was underpinned by the constructivist approach. The researcher considered triangulation of methods when gathering data due to the comprehensiveness of the sought data. The method employed was to gather literature on similar studies conducted by scholars elsewhere to shed light to the researcher of the problem under investigation. Structured questionnaires, semi-structured interviews, participant observations were used to collect data on focal learning and teaching activities. The researcher was keen in determining how teachers employed their preferred methods of teaching geography and the attitudes and perceptions of the learners to the activities that were part of the lessons. The researcher involved (n=16) subject teachers, and administered a 20-item questionnaire to learners. (n=407) responded to a 15-item questionnaire. Curriculum teachers (n=10) were interviewed separately from the pool of the said (n=16), subject advisers (n=2) were interviewed to provide first-hand experience. The findings affirmed that there was poor professional proficiency; textbooks were a recognized learning barrier to second language English learners in terms of the difficulty of the language which was linked to geographical concepts coined in English, teachers’ lack of linguistic competence in LoLT to supplement the difficult textbooks. The result was that this led to resorting to code-switching that deprived learners of practice in the language to attain effective learning and good performance in examinations.
Thesis (Ph. D. (Education)) -- University of Limpopo, 2016
Keywords: Geography learning; Learning barriers; 370.71270968; Education,Secondary -- South Africa -- Limpopo; Education-Curricula -- Research -- South Africa -- Limpopo